MEWUJUDKAN MAKAN BERGIZI GRATIS: PERSPEKTIF GURU SD DALAM IMPLEMENTASI KEBIJAKAN - Furkan, Izzan Muhammad; Sari, Ratu Amalia; Eliza, Mimi Fitria; Nofrizal, Doni; Junva, Fadilla; Gistituati, Nurhizrah; Anisah, Anisah (Jurnal Manajemen Pendidikan, 2025)
The Free Nutritious Meal Program (MBG) is one of the Indonesian government's strategic initiatives under the leadership of President Prabowo Subianto, aimed at improving the nutritional status of school-age children and strengthening the foundation of education in preparation for the Golden Generation 2045. This article critically analyzes the implementation of the MBG program, focusing on the perspectives and experiences of elementary school teachers as key actors in educational institutions. The research employs a qualitative approach through literature review. The findings indicate that the program is well-received by teachers as it is perceived to enhance student motivation, improve attendance, and support daily nutritional intake, particularly in underdeveloped areas. However, challenges exist in terms of logistics, inadequate school infrastructure, and the program's insufficient integration with teaching and the curriculum. A philosophical analysis based on rationalism indicates that this policy represents a rational decision based on the actual needs of society, although it still faces limitations in rationality during implementation (bounded rationality). From a public policy ethics perspective, the MBG program reflects the principles of justice and social equity, but requires improvements in transparency, accountability, and fiscal sustainability to avoid overburdening the national budget.